dr/dΩ+rTanΩ=cos2Ω
Let us solve the differential equation "\\frac{dr}{d\u03a9}+r\\tan\u03a9=\\cos2\u03a9.\\\\"
Firstly, let us divide both parts by "\\cos\\Omega." Then we have the differential equation
"\\frac{1}{\\cos\\Omega}\\frac{dr}{d\u03a9}+r\\frac{1}{\\cos\\Omega}\\tan\u03a9=\\frac{1}{\\cos\\Omega}\\cos2\u03a9,"
which is equivalent to the equation
"\\frac{1}{\\cos\\Omega}\\frac{dr}{d\u03a9}+r\\frac{\\sin\\Omega}{\\cos^2\\Omega}=\\frac{1}{\\cos\\Omega}(\\cos^2\u03a9-\\sin^2\u03a9),"
and hence "(r\\frac{1}{\\cos\\Omega})'=\\cos\u03a9-\\frac{\\sin^2\u03a9}{\\cos\\Omega}."
It follows that
"r\\frac{1}{\\cos\\Omega}=\\int(\\cos\u03a9-\\frac{\\sin^2\u03a9}{\\cos\\Omega})d\\Omega"
"=\\sin\\Omega-\\int\\frac{\\sin^2\u03a9}{\\cos^2\\Omega}d(\\sin\\Omega)"
"=\n\\sin\\Omega+\\int\\frac{\\sin^2\u03a9}{\\sin^2\\Omega-1}d(\\sin\\Omega)"
"=\n\\sin\\Omega+\\int\\frac{\\sin^2\u03a9-1+1}{\\sin^2\\Omega-1}d(\\sin\\Omega)"
"=\n\\sin\\Omega+\\sin\\Omega+\\int\\frac{1}{\\sin^2\\Omega-1}d(\\sin\\Omega)"
"=\n2\\sin\\Omega+\\frac{1}{2}\\int(\\frac{1}{\\sin\\Omega-1}-\\frac{1}{\\sin\\Omega+1})d(\\sin\\Omega)"
"=\n2\\sin\\Omega+\\frac{1}{2}(\\ln|\\sin\\Omega-1|-\\ln|\\sin\\Omega+1|)+C"
"=\n2\\sin\\Omega+\\frac{1}{2}\\ln|\\frac{\\sin\\Omega-1}{\\sin\\Omega+1}|+C."
Therefore, the general solution is
"r= 2\\sin\\Omega\\cos\\Omega+\\frac{1}{2}\\cos\\Omega\\ln|\\frac{\\sin\\Omega-1}{\\sin\\Omega+1}|+C\\cos\\Omega"
or
"r=\n\\sin2\\Omega+\\frac{1}{2}\\cos\\Omega\\ln|\\frac{\\sin\\Omega-1}{\\sin\\Omega+1}|+C\\cos\\Omega."
Comments
Leave a comment